Implementation Of An Inventory System For A Conventional Wholesale Store Using The Codeigniter Framework - Naufal Yusron Wildan Ramadhan; Maryam Maryam (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Toko Nor'In, a mid-range grocery store founded in 1999, operates as a wholesale outlet supplying necessities and staple foods, while also catering directly to consumers. The store provides delivery services to downlines or loyal customers within the Tengaran District area. Despite its operations, Toko Nor'In still relies on a manual stock recording system, which frequently leads to serious problems like data inaccuracies and low operational efficiency. Implementing a computerized system is a vital solution to lighten the workload of employees and provide significant benefits for the grocery business. The new inventory system was developed using the Waterfall method, a structured approach following four distinct stages: requirement definition, system design, implementation, and testing. This method ensures clear guidance and efficient management, guaranteeing a system that meets user expectations. The information system was constructed utilizing the PHP programming language, Visual Studio Code, and SQL. To verify its quality, the system underwent Black Box testing and System Usability Scale (SUS) testing. Black Box results confirmed the website's functionality works optimally. Furthermore, the system achieved a SUS score of 69, categorized as